Settlement suitability mapping based on the salinity index in the Banda Aceh City - Muhammad Rusdi; Muhammad Irham; Sugianto Sugianto; Ruhizal Roosli; Mohd Sanusi S Ahamad; Yudi Haditiar (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2021)
The availability of accurate land data is useful in planning, policymaking, regional development, and preserving the environment. Banda Aceh is the center of education and development in Aceh, Indonesia, which is located in the coastal area. The tsunami has had a significant impact on development and settlements in Banda Aceh. Currently, settlements in Banda Aceh rapidly grow also the need for land and water resources. Therefore, mapping the potential for residential land in Banda Aceh is required. This study examines land suitability in Banda Aceh based on the FAO salinity criteria and spatial data analysis by remote sensing methods. Based on the results, it is known that Banda Aceh has land suitable for settlement of around 85% or 2975 hectares. These areas are generally located close to watersheds and receive sufficient freshwater input. Meanwhile, areas far from rivers and close to the coast have brackish salinity. This area is not suitable as a residential area. There are about three sub-districts in Banda Aceh which are not suitable for settlement.Keywords:KrigingRemote sensingSettlementSalinity mappingCoastalBanda Aceh